Characteristics of the corrosion products on three scratched heat-resisting alloys in closed-loop supercritical and high-temperature CO2. (15th April 2022) - Guo, Tingshan; Xu, Yiming; Liu, Shijie; Liang, Zhiyuan; Zhao, Qinxin
Abstract: The characteristics of the corrosion products on scratched T92, TP347HFG, and IN625 in a closed-loop and flowing supercritical CO2 at 600 °C were investigated. Severe exfoliation of oxide scale was found on TP347HFG, causing weight loss during testing. Irregular and crystal oxides were found on IN625 and were primarily attributed to the evaporation of Mo oxides. The CO2 pressure affected the corrosion weight gain and structural distribution of corrosion products on the investigated materials by controlling the ratio of CO and CO2 . The scratches accelerated the corrosion of all alloys due to the micro-cracks induced during scratching. Highlights: Corrosion of scratched alloys in closed-loop supercritical CO2 was investigated. Severe exfoliation of oxide scale was found on TP347HFG and IN625. The CO2 pressure affected the corrosion via controlling the ratio of CO and CO2 . The scratch accelerated the corrosion of all materials due to the micro-cracks induced by the scratch process.